Draft Annual Plan 1989-90 Seventh Five Year Plan 1985-90 - Planning Commission (Planning Commission, 1989)
The objective of the scheme is to demonstrate the farmers about production potentialities of every unit of land by using high yielding varieties of crops and by adopting Multiple Cropping pattern with the latest technology in package of practice. Besides, the scheme serves as a teaching tool for training the farmer.
Centrally sponsored schemes Union Territory of Pondicherry